2000
DOI: 10.1046/j.1570-7458.2000.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface films as mosquito larvicides: partitioning the mode of action

Abstract: Oils and other surface films used against mosquito larvae may act by flooding the tracheal system with oil, by disrupting the surface forces that allow larvae to rest at the surface, by toxicity, or by eliciting chemosensory responses. In an attempt to identify diagnostic symptoms of these modes of action we treated fourth‐stage larvae of Culex pipiens L. form molestus Forskål (Diptera: Culicidae: Culicinae) with agents operating in a single mode (Ondina oil for flooding with oil, nicotine for toxicity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
3
25
0
Order By: Relevance
“…On the contrary, other studies revealed that methanolic extracts were less effective than the extracts of other essential oils 3 . Researchers suggested that larvicides affect mosquito in one of three possible mechanisms; by physical flooding of the tracheal system or by toxicity specially that of volatile components and by interference with surface forces 10 . Different sensitivities of mosquito species towards different volatile oils has been also recorded 3 .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other studies revealed that methanolic extracts were less effective than the extracts of other essential oils 3 . Researchers suggested that larvicides affect mosquito in one of three possible mechanisms; by physical flooding of the tracheal system or by toxicity specially that of volatile components and by interference with surface forces 10 . Different sensitivities of mosquito species towards different volatile oils has been also recorded 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Larvicides target larvae in the breeding habitat before they can mature into adult mosquitoes and disperse. Corbet et al (2000) suggested that conventional larvicidals affect mosquito larvae in one or more of three possible modes: by physical flooding of the tracheal system, by toxicity (especially that of volatile components) and by interference with surface forces. Larvicides include the bacterial insecticides Bacillus thuringiensis and Bacillus sphaericus, the insect growth inhibitor methoprene and the organophosphate insecticide temephos.…”
Section: Introductionmentioning
confidence: 99%
“…After 6 h, however, alterations in siphonal valves and trachea were observed; dead larvae were discarded. Tracheal segments from the thorax and abdomen were translucent, which is indicative of the presence of liquid in these areas 38. In contrast, larvae in the control group presented an intact and darkened trachea, which is indicative of the presence of air only.…”
Section: Resultsmentioning
confidence: 91%